Prosocial : using evolutionary science to build productive, equitable, and collaborative groups - Atkins, Paul W. B.; Wilson, David Sloan; Hayes, Steven C. (Context Press, 2019)
Based on the work of Nobel Prize winning economist, Elinor Ostrom, Prosocial presents a groundbreaking and comprehensive program for designing effective and socially equitable groups of all sizes to create positive world change--from businesses and social justice groups to global organizations.